Korelasi Motivasi Kerja Terhadap Kinerja Pegawai Satuan Polisi Pamong Praja Provinsi Jawa Timur - Windy Nur Ramadhina; Tukiman Tukiman (Jurnal Ilmu Sosial dan Ilmu Politik)
Work motivation is often overlooked, even though it is an important factor in organizations such as the Civil Service Police Unit (Satpol PP) in East Java. Work motivation is crucial for public employees, especially members of Satpol PP, as they play a significant role in protecting the community and maintaining public peace and order, thereby requiring optimal employee performance. According to the East Java Governor Regulation No. 43 of 2021, the Satpol PP of East Java Province has an important role and obligation to enforce the law at the regional level. This study aims to determine the relationship between work motivation and employee performance in the Satpol PP of East Java Province. The study uses a quantitative approach with Pearson product-moment correlation to test the relationship between work motivation and employee performance in the Satpol PP of East Java Province. The research data were obtained from 65 respondents selected using the Solvin formula. The results show a very strong relationship between work motivation and employee performance in the Satpol PP of East Java Province, with a correlation test result of 0.843.